2020
DOI: 10.30659/odj.7.2.90-96
|View full text |Cite
|
Sign up to set email alerts
|

Ekstrak Daun Salam Dalam Meningkatkan Ekspresi Fibroblast Growth Factor Pada Ulkus Traumatik Rongga Mulut

Abstract: Background: Traumatic ulcers are lesions of the oral mucosa caused by mechanical, chemical, and temperature trauma. Traumatic ulcer treatment aims to reduce inflammation, accelerate the healing process, and reduce pain. Bay leaf has anti-inflammatory pharmacological activities. This study aims to determine the effect of bay leaf extract on the expression of fibroblast growth factor in traumatic ulcer oral mucosa in Wistar rats. Method: This is an experimental research with a post-test only control group design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…Fetal bovine serum and KOSR have vitamins/antioxidants and proteins that can increase FGF mRNA relative expression, leading to increased proliferation, differentiation, and migration of fibroblasts that contribute to a faster wound-healing process. (15) The presence of serum in cell culture constitutes an extracellular stimulatory process that uses intracellular signals via the Rho-actin/myocardin-related transcription factor (MRTF) and Ras ERK/ternary complex factor (TCF) pathways. These factors act as a cofactor for serum response factor (SRF) in the nucleus to regulate cell differentiation, migration, motility, proliferation, cytoskeleton, signaling, adhesion, development, myogenesis, apoptosis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Fetal bovine serum and KOSR have vitamins/antioxidants and proteins that can increase FGF mRNA relative expression, leading to increased proliferation, differentiation, and migration of fibroblasts that contribute to a faster wound-healing process. (15) The presence of serum in cell culture constitutes an extracellular stimulatory process that uses intracellular signals via the Rho-actin/myocardin-related transcription factor (MRTF) and Ras ERK/ternary complex factor (TCF) pathways. These factors act as a cofactor for serum response factor (SRF) in the nucleus to regulate cell differentiation, migration, motility, proliferation, cytoskeleton, signaling, adhesion, development, myogenesis, apoptosis, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The results of a study concluded that 10% bay leaf extract in a cream preparation had an inflammatory effect on carrageenin-induced rat paw edema 10. In another study, 10% bay leaf extract gel was found to affect several inflammatory mediators, such as decreasing TNF-α gene expression and increasing IL-10 and FGF gene expression [15][16][17] . However, there are yet to be many studies that prove the effect of bay leaves on traumatic ulcers, especially on IL-6 and IL-10 gene expression.…”
Section: Introductionmentioning
confidence: 95%
“…Salah satu bentuk aplikasi pengobatan dengan tanaman obat adalah pengobatan pada luka yang sering dilakukan oleh masyarakat. 4 Salah satu tanaman yang digunakan oleh masyarakat untuk mengobati luka adalah tanaman Jatropha multifida L. 5 Jatropha multifida L. dikenal sebagai tanaman betadine. 3 Tanaman betadine oleh banyak masyarakat Sumatera Selatan digunakan sebagai tanaman hias, sebagian masyarakat ada yang menggunakan sebagai tanaman untuk obat luka.…”
Section: Pendahuluanunclassified